Clinical decision making in hypertension: a survey of attitudes of family physicians in the Lisbon health region (Portuguese Journal of Family Medicine and General Practice, 2015)
Objectives: This study was designed to characterize the attitudes of family physicians regarding clinical decision making in hypertension, including issues related to monitoring and treatment and to compare these attitudes with clinical recommendations available at the time of the study. Type of study: Cross-sectional study. Setting: Primary health care centers in Lisbon and Vale do Tejo, Portugal. Population: Family physician specialists and trainees in family medicine. Methods: Self-completed questionnaire assessing variables related to demographic characteristics, experience of treating hypertensive patients, measurement of blood pressure (BP), lifestyle changes, the decision to initiate antihypertensive drugs, and strategies used when assessing patient adherence. Bivariate analysis (Chi-square tests, α=0.05) was used to explore the associations between clinical decision-making and other variables. Results: The 60 participants (41 females) from 14 Primary Health Care Centers had a mean age of 52±8.6 years and a mean of 22±8.2 years experience in practice. All physicians considered lifestyle change to be useful. Acceptable ambulatory BP (ABPM) was 136/83mmHg for the daytime value. The BP values chosen for initiation of treatment were BP>140/90mmHg for patients without other risk factors. In the elderly, 77% of physicians agreed with accepting higher BP values, initiating treatment when BP>150/90mmHg. Physicians preferred to initiate therapy with only one drug. Most physicians (58%) believed that many patients can achieve control of BP with only one drug and physicians with over 20 years of experience in practice tended to agree more with this statement (p=0.043). Conclusions: The reported attitudes were in line with the national and European clinical guidelines available at the time of the study regarding the usefulness of lifestyle changes and the BP values chosen for initiating treatment. There was some heterogeneity regarding management of BP in the elderly and ABPM values. Updating of clinical recommendations requires continuous training of family physicians, in order to incorporate the best options for management of hypertension in clinical practice.
Keywords: Hypertension; Decision Making; Clinical Guidelines; Physician-patient Relations